Pemikiran Pendidikan K.H. Ahmad Dahlan dan relevansinya dengan dunia pendidikan modern - Ratnawati, Eka; Hendratno; Istiq’faroh, Nurul (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
This study aims to explore the insight essence of KH. Ahmad Dahlan and its relevance to the world of modern education as a pioneer of education. The research was qualitatif approach in the form of library research. The collection technique is by documentation, document analysis. The technique of analyzing descriptive data is verification and drawing conclusions. The results of this study are the educational thinking of KH. Ahmad Dahlan combines religious knowledge and general knowledge. Teacher exchange, long life long education, teacher competence, teacher learning program. Social competence, leadership, cosmopolitan open social competence.